2011
DOI: 10.1016/j.jtv.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts and myofibroblasts in wound healing: Force generation and measurement

Abstract: Fibroblasts are one of the most abundant cell types in connective tissues. These cells are responsible for tissue homeostasis under normal physiological conditions. When tissues are injured, fibroblasts become activated and differentiate into myofibroblasts, which generate large contractions and actively produce extracellular matrix (ECM) proteins to facilitate wound closure. Both fibroblasts and myofibroblasts play a critical role in wound healing by generating traction and contractile forces, respectively, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
343
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(364 citation statements)
references
References 81 publications
9
343
0
12
Order By: Relevance
“…VEGF is responsible for initiating vessel formation and inducing molecular and cellular events leading to network stabilization and maturation (39). VEGF inhibition in a coculture of ECs and fibroblasts was predicted to damage the network only whereas the level of forces could be maintained by the fibroblasts (19,40,41). However, the presented results suggest that the force measured during network assembly is applied by both cell types, which provide a synergistic effect on overall force when collaborating to form elongated tubes.…”
Section: Discussionmentioning
confidence: 79%
“…VEGF is responsible for initiating vessel formation and inducing molecular and cellular events leading to network stabilization and maturation (39). VEGF inhibition in a coculture of ECs and fibroblasts was predicted to damage the network only whereas the level of forces could be maintained by the fibroblasts (19,40,41). However, the presented results suggest that the force measured during network assembly is applied by both cell types, which provide a synergistic effect on overall force when collaborating to form elongated tubes.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, CD20 antigen is an activated-glycosylated . The major source of myofibroblasts in skin wounds is the fibroblasts recruited from dermis and subcutaneous tissues surrounding the wound, but pericytes and vascular smooth muscle cells are also potential able to differentiate into myofibroblasts 15,16 . In this study, the immunohistochemical expression of α-SMA in stromal cells permeating collagen fibers was interpreted as positive markers of myofibroblasts, whereas stained cells surround blood vessels was considered consist with pericytes and then discarded.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, further reduction of myofibroblasts number seems to occur in response to apoptosis mediated by progressive decrease in local levels of TGF-β 16 . Studies have demonstrated that myofibroblasts are essential to wound healing since there is a direct correlation between the wound tension strength, as well as wound contraction rates, and myofibroblasts differentiation 15 . Type I collagen is the major extracellular matrix compound of the dermal and mucosal connective tissues and it is fundamental to ensure the optimal mechanical properties of the healing scar.…”
Section: Resultsmentioning
confidence: 99%
“…28 Additionally it is known that, contraction of fibroblasts in certain connective tissues plays a critical role in the closure of skin wounds during healing. [29][30][31][32] Statistically significant increase of α-SMA in ABS group represents an accelerating action for wound healing, reflecting increased tissue contraction which results in decreased area of the wound. ABS effect over α-SMA separately may be the most important point for ABS' mode of action in accelerating the wound healing rate by decreasing the wound area.…”
Section: Discussionmentioning
confidence: 99%